Relevance of Fc Gamma Receptor Polymorphisms in Cancer Therapy With Monoclonal Antibodies - Mata-Molanes, Juan J.; Rebollo-Liceaga, Joseba; Martínez-Navarro, Elena Mª; Manzano, Ramón González; Brugarolas, Antonio; Juan, Manel; Sureda, Manuel (Frontiers in Oncology, 2022)
Therapeutic monoclonal antibodies (mAbs), including immune checkpoint inhibitors (ICIs), are an important breakthrough for the treatment of cancer and have dramatically changed clinical outcomes in a wide variety of tumours. However, clinical response varies among patients receiving mAb-based treatment, so it is necessary to search for predictive biomarkers of response to identify the patients who will derive the greatest therapeutic benefit. The interaction of mAbs with Fc gamma receptors (FcγR) expressed by innate immune cells is essential for antibody-dependent cellular cytotoxicity (ADCC) and this binding is often critical for their in vivo efficacy. FcγRIIa (H131R) and FcγRIIIa (V158F) polymorphisms have been reported to correlate with response to therapeutic mAbs. These polymorphisms play a major role in the affinity of mAb receptors and, therefore, can exert a profound impact on antitumor response in these therapies. Furthermore, recent reports have revealed potential mechanisms of ICIs to modulate myeloid subset composition within the tumour microenvironment through FcγR-binding, optimizing their anti-tumour activity. The purpose of this review is to highlight the clinical contribution of FcγR polymorphisms to predict response to mAbs in cancer patients.